2011
DOI: 10.1042/bsr20100126
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a Ca2+-dependent novel lectin from Nymphaea nouchali tuber with antiproliferative activities

Abstract: A lectin (termed NNTL) was purified from the extracts of Nymphaea nouchali tuber followed by anion-exchange chromatography on DEAE-cellulose, hydrophobic chromatography on HiTrap Phenyl HP and by repeated anion-exchange chromatography on HiTrap Q FF column. The molecular mass of the purified lectin was 27.0 ± 1.0 kDa, as estimated by SDS/PAGE both in the presence and in the absence of 2-mercaptoethanol. NNTL was an o-nitrophenyl β-D-galactopyranoside sugar-specific lectin that agglutinated rat, chicken and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…Multiplication of cancer cells was stopped by several kinds of plant lectin (Liu et al 2010) and due to the differences in their sugar specificity, each lectin exhibits differences in their antiproliferative effect against tumor cell lines. Several experiments were made to study the anticancer effect of lectins on different cancer cells (Liu et al 2010) but only a few reported against EAC cells (Ahmed et al 1988;Kabir et al 2011aKabir et al ,b, 2012Akev et al 2007). In the present study MTT assay was performed and the result showed that Pea lectin inhibited EAC cells proliferation in vitro in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Multiplication of cancer cells was stopped by several kinds of plant lectin (Liu et al 2010) and due to the differences in their sugar specificity, each lectin exhibits differences in their antiproliferative effect against tumor cell lines. Several experiments were made to study the anticancer effect of lectins on different cancer cells (Liu et al 2010) but only a few reported against EAC cells (Ahmed et al 1988;Kabir et al 2011aKabir et al ,b, 2012Akev et al 2007). In the present study MTT assay was performed and the result showed that Pea lectin inhibited EAC cells proliferation in vitro in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Growth inhibition of EAC cells was also studied by using different lectins. Jackfruit lectin inhibited only 21.8, 40.2 and 57.5% of EAC cell growth at 50, 100 and 150 g/day respectively; Kaempferia rotunda lectin inhibited 51 and 67% of cell growth at 1.25 mg/kg/day and 2.5 mg/kg/day respectively; Trichosanthes cucumerina seed lectin (TCSL) showed 28 and 72% growth inhibition against EAC cells at 1 mg/kg/day and 2 mg/kg/day respectively and Nymphaea nouchali tuber lectin (NNTL) showed 56 and 76% growth inhibition against EAC cells at 1.5 mg/kg/day and 3.0 mg/kg/day respectively (Ahmed et al 1988;Kabir et al 2011aKabir et al ,b, 2012. In tumor-bearing mice, anemia occurs due to the decrease in RBC or hemoglobin percentage and increased the WBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell growth inhibition in vivo. To determine the cell growth inhibition properties of the compound, five groups of Swiss albino mice (n = 6) weighing 25 ± 4 g were used (Kabir et al, 2011). To assess the therapeutic evaluation, 1 × 10 6 EAC cells were inoculated into each group of mice on day 0.…”
Section: Methodsmentioning
confidence: 99%